College of American Pathologists EQAS for Luminex Antibody Test in a Stand -Alone Accredited Indian Laboratory - Mahendra Narain Mishra; Vandana Lal (Archives of Organ Transplantation - Peertechz Publications, 2016)
Luminex antibody detection, especially Luminex crossmatch is used frequently in India for pretransplant work up for patients with end stage renal disease. This test is often performed in lieu of single antigen bead assay in India due to its lower cost. We report on our experience with College of American Pathologist external proficiency test samples (CAP EQAS) for Luminex based antibody detection assays. Methods: Twelve surveys from College of American Pathologists (MX-1 A, B, C) each comprising of either four plasma samples for HLA - class I, two samples for HLA - class II (MX- 2 A, B and C) and two sets of whole blood containing non enriched lymphocytes were processed as per schedule from January 2014 till December 2014 for detection of HLA class I or/and HLA class II IgG antibodies.  Results: All six surveys were fully concordant for antibody screening which is a pooled bead assay: greater than ninety percent samples of phenotype test were accurately assigned, but six samples (16.67%) of Luminex T cell crossmatch were discordant of which five samples were incorrectly assigned negative possibly due to matrix interference.  Conclusion: CAP EQAS survey was adequate for external quality control of Luminex antibody assays except for Luminex crossmatch test. This could be due to matrix interference and such discordant results need to be correlated by inter-lab comparison until CAP is able to provide suitable samples.